Implementation of Trauma-Informed Care Strategies in a Multidisciplinary Maternal-Fetal Care Center [A186]. (May 2022) - Cole, Joanna CM; Zajac, Lindsay; Budney, Alexandra; Spinner, Susan; Schindewolf, Erica; Teefey, Christina Paidas
Abstract : INTRODUCTION: Little is known about traumatic stress among expectant parents who receive a prenatal diagnosis of a birth defect. The current study aimed to identify traumatic stress symptoms among expectant parents carrying fetuses with confirmed fetal anomalies and describe the ways in which a fetal care center, with an embedded psychosocial support team, provides trauma-informed strategies to mitigate the effects of trauma throughout the pregnancy via collaborative prenatal care visits. METHODS: A retrospective analysis of 4, 391 pregnant patients and 3, 570 partners in a fetal center was performed with institutional review board approval. Traumatic stress symptoms in response to the confirmed fetal diagnosis were assessed using the Impact of Events Scale–Revised (IES-R). Exploratory descriptive analyses examined rates of overall traumatic stress symptoms and elevated subscale scores. RESULTS: In total, 28.7% of mothers and 24.2% of fathers reported elevated traumatic stress symptoms in response to their confirmed fetal diagnosis, with clinically significant risk endorsed among 16.2% and 13.4% respectively. Symptoms of intrusion and avoidance were most notable among parents. Trauma-informed care strategies provided by a multidisciplinary care team, in collaboration with the psychosocial support team to identify, support, and intervene with high-risk parents, were implemented. CONCLUSION: Recognizing that expectant parents who receive a fetal anomaly diagnosis are at heightened risk for experiencing traumatic stress symptoms, maternal–fetal care teams should implement trauma-informed care into daily prenatal clinical practice and incorporate psychosocial support services, including parental mental health screening, psychosocial assessment, and clinical interventions, to reduce the negative effects of trauma for parents prior to birth.